(untitled) (Ciudades, 2018)
This text comes across the critical situation of the present day society through the concepts of landscape and sustainable development, emphasizing the need to prevent their values, common goods, from being socially reduced to those of the dominant members. Only that interpretation of the sustainable development made in terms of the progress of the whole society proves to be valid. The landscape concept, which cultural schema is essential for individuals to understand their environment, summarizes the infinite values and the ecological and social systems the sustainable development is strongly related to, and therefore must respect. The author enhances the role that the State must play in the administration of these common goods; conditions helping to the sustainable development of a landscape are enunciated as well.